THE ROLE OF LOCAL SOURCE MATERIALS IN FOSTERING A LOVE FOR LOCAL HISTORY: PERSPECTIVES OF SMAN 1 MEDAN STUDENTS - Anisa, Tihaya; Sumantri, Pulung; Arif, Toni (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research aims to explore the role of local source material in fostering a love of local history from the perspective of students at SMA Negeri 1 Medan. The research method used is qualitative, with a phenomenological approach. Data was collected through in-depth interviews with 15 students selected using purposive sampling. Data analysis was carried out using thematic coding techniques. The research results show that local source materials have a significant role in increasing students' interest in and love for local history. Factors such as relevance, depth of understanding, and direct experience with local source material influence students' perceptions of the importance and relevance of local history in their lives. This research provides implications for the development of a more inclusive and locally based history curriculum to strengthen students' cultural and national identities. In conclusion, this research makes a significant contribution to the development of a more inclusive and locally-based history curriculum at SMA Negeri 1 Medan. By understanding more deeply the role of local source materials in fostering a love of local history, we can design learning experiences that are more relevant and engaging for students and help strengthen their cultural and national identities.